Rapid molecular detection of Senecavirus A based on reverse transcription loop-mediated isothermal amplification (RT-LAMP) and CRISPR/Cas12a - Jiang, Chenghui; Wang, Huibao; Guo, Rongxia; Yang, Rui; Li, Xiaoming; Liu, Ping; Wang, Jing; Yang, Jincai; Chang, Yanyan; Zeng, Qiaoying (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionSenecavirus A (SVA), an emerging vesicular pathogen, is responsible for porcine idiopathic vesicular disease (PIVD). This disease is closely associated with porcine vesicular disease and acute neonatal piglet mortality, presenting a substantial threat to the global swine industry. At present, the absence of effective drugs or vaccines for treating the disease makes accurate diagnosis of SVA of paramount importance for the effective prevention and control of the disease.MethodsIn this study, we combined reverse transcription loop-mediated isothermal amplification (RT-LAMP) and Clustered Regularly Interspaced Short Palindromic Repeats and CRISPR-associated protein12a (CRISPR/Cas12a) using a dual-labelled fluorescence quencher or fluorescent biotin single-stranded DNA reporter molecule to develop two rapid, reliable, and portable visual SVA assays: RT-LAMP-Cas12a-FQ and RT-LAMP-Cas12a-FB.ResultsThe two methods exhibited comparable detection limits, with 9.6 copies/μL achieved in 40 and 45 minutes, respectively. They did not cross-react with non-target nucleic acids extracted from other related viruses and showed high specificity for SVA RNA detection. Furthermore, the methods demonstrated satisfactory performance in detecting 69 porcine adventitious samples, with no significant differences from that of quantitative reverse transcription polymerase chain reaction (RT-qPCR).DiscussionIn summary, the RT-LAMP-Cas12a-FQ and RT-LAMP-Cas12a-FB methods developed are promising for early detection and routine surveillance of porcine SVA in resource-poor areas.